Predictive modelling of 2‐year potency outcomes using a novel 90‐day erection fullness scale after robot‐assisted radical prostatectomy. (14th April 2018) - Huynh, Linda M.; Osann, Kathryn; Skarecky, Douglas; Ahlering, Thomas E.
Abstract : Objective: To introduce a patient‐reported erection fullness scale (%fullness) after robot‐assisted radical prostatectomy (RARP) as a qualitative adjunct to the five‐item version of the International Index of Erectile Function (IIEF‐5) and as a 90‐day predictor of 2‐year potency outcomes. Patients and Methods: Prospective data were collected from 540 men with preoperative IIEF‐5 scores of 22–25 who underwent RARP by a single surgeon, and of whom 299 had complete data at all time points up to 2 years. In addition to standard assessment tools (IIEF‐5 and erections sufficient for intercourse [ESI]), the men were asked to 'indicate the fullness you are able to achieve in erections compared to before surgery?' (range: 0–100%). The primary outcome was prediction of potency (defined as ESI) at 24 months, based on 90‐day %fullness tertile (0–24%, 25–74% and 75–100%). Results: A total of 299 men with complete follow‐up were included in the study. Significant predictors of 24‐month potency included age, body mass index, pathological stage, nerve‐sparing status and %fullness tertiles. When the men (preoperative IIEF‐5 score 22–25) were assessed at 90 days after RARP, 181/299 (61%) had erections inadequate for intercourse. If IIEF‐5 scores of 1–6 were used, 142/181 men (78%) would be targeted for early intervention. By contrast, if 0–24% fullness was used, 88/181 men (49%) would be targeted. If both the IIEF‐5 score and %fullness were used, this would be reduced to 77/181 men (43%). Conclusions: We introduce %fullness as a qualitative adjunct to the IIEF‐5 score, and separately as a 90‐day predictor of 2‐year potency recovery. This initial report is hypothesis‐generating, such that the use of %fullness enables the identification of men who are most likely to benefit from early, secondary intervention.